Does the effectiveness of the Fintech platform affect interest in paying infaq and sadaqah? - Kamila Dhiyanahda Arelsa; Muhammad Sholahuddin (Sebelas Maret Business Review, 2023)
The rapid adoption of digital technology has revolutionized various industries, including the financial services sector, through the emergence of financial technology (Fintech). In Indonesia, Fintech regulations, such as Indonesian bank (Bank Indonesia-BI) regulations no. 18/40/PBI/2016 has played a crucial role in governing payment systems. This research examines the impact of the Fintech platform's effectiveness on individuals' interest in making infaq and sadaqah payments. A survey method was employed, utilizing a sample size of 128 individuals residing in the Solo Raya area, and conducted via Google form. The study results indicate that the Fintech platform's effectiveness significantly influences individuals' interest in making infaq or sadaqah payments. This can be attributed to the trust people place in Fintech platforms, which ensures data confidentiality and minimizes the risk of fraud. Consequently, individuals are more inclined to engage in infaq and sadaqah payments, recognizing Fintech platforms' secure and reliable nature. This research highlights the positive relationship between Fintech platform effectiveness and individuals' interest in infaq and sadaqah payments, shedding light on the potential for Fintech to drive the development of the Islamic economy further.